Electronic Circuit of a New Simple 6D Hyperchaotic System with Two Saddle--Foci Equilibria - Al-Azzawi, Saad Fawzi; Aziz, Shua'a M. (Journal of Applied Nonlinear Dynamics, 2026)
A new simple 6D hyperchaotic system (high dimension) with four positive ($4+ve$) Lyapunov exponents (LEs) is constructed via coupling between a 1D nonlinear system and a 5D system. The proposed system is considered simple because it consists of thirteen terms only, two of which are quadratic nonlinearly with two coupling parameters. This 6D system has two unstable equilibria points and belongs to the self-excited attractors. This system exhibits the highest Lyapunov exponents and Kaplan-Yorke dimension compared to the 13 other 6D systems in existing literature. The new system's dynamical analysis is investigated theoretically and numerically, including equilibria points, divergence, Lyapunov exponents, Lyapunov dimension, phase portrait, coexisting attractors, and electronic circuit. Thereafter, complete synchronization (CS) between two identical 6D systems had been achieved.